1990
DOI: 10.1115/1.2927680
|View full text |Cite
|
Sign up to set email alerts
|

Local Heat Transfer in Internally Cooled Turbine Airfoil Leading Edge Regions: Part I—Impingement Cooling Without Film Coolant Extraction

Abstract: An experimental study has been designed and performed to measure very localized internal heat transfer characteristics in large-scale models of turbine blade impingement-cooled leading edge regions. Cooling is provided by a single line of equally spaced multiple jets, aimed at the leading edge apex and exiting the leading edge region in the opposite or chordwise direction. Detailed two-dimensional local surface Nusselt number distributions have been obtained through the use of aerodynamically steady but therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(49 citation statements)
references
References 0 publications
1
47
0
1
Order By: Relevance
“…Several papers concerned with impinging jets on concave surfaces are available [6][7]. Bunker and Metzger [6] find out a general increase in heat transfer with decreasing the leading edge sharpness as well as with decreasing the nozzle to apex distance, and increase in span-wise average heat transfer with decreasing the jet pitch to diameter ratio.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several papers concerned with impinging jets on concave surfaces are available [6][7]. Bunker and Metzger [6] find out a general increase in heat transfer with decreasing the leading edge sharpness as well as with decreasing the nozzle to apex distance, and increase in span-wise average heat transfer with decreasing the jet pitch to diameter ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Bunker and Metzger [6] find out a general increase in heat transfer with decreasing the leading edge sharpness as well as with decreasing the nozzle to apex distance, and increase in span-wise average heat transfer with decreasing the jet pitch to diameter ratio. Fenot et al [7] study the heat transfer due to a row of hot jets impinging on a concave surface and present correlations of effectiveness and Nusselt number at stagnation points.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heat transfer coefficients for the jet wall may be up to 50% of those for the target wall. Bunker and Metzger (1990), (1996) presented local mass transfer data by using a naphthalene sublimation technique for a single row of circular jets with radially outward cross flow in the leading edge region of a rotating blade. They showed that rotation reduces the heat/mass transfer coefficients between 10% and 40% depending on the rotating angle.…”
Section: Direction Of Rotationmentioning
confidence: 99%
“…By conducting experiments when a single row of jet impinges on a concave surface with extraction of film coolant, Bunker and Metzger [10,11] noted that the flow extraction showed only a small influence on heat transfer. They also pointed out that the jets inline with film holes would yield higher heat transfer coefficient than when they are in staggered configuration.…”
Section: Introductionmentioning
confidence: 99%